2011
DOI: 10.1016/j.optmat.2010.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of nano- and macrosized LaPO4:Ce,Tb excited by synchrotron radiation

Abstract: Tb 3+Nanocrystals Luminescence Synchrotron radiation a b s t r a c tComparing the luminescence properties of nanosized and macroscopic LaPO 4 :Ce,Tb powders are performed in wide spectral range using synchrotron radiation. In the present study, LaPO 4 :Ce,Tb nanopowder was produced by means of a microwave-induced synthesis in ionic liquids, whereas the bulk sample represents a commercial lamp phosphor. Emission and excitation of both, Ce 3+ and Tb 3+ luminescence, is observed to be different when comparing bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…VUV excitation luminescence spectroscopy is especially a powerful tool for investigating wide band gap materials such as fluorides [27], iodides [28] and oxides [29][30][31][32]. The method was extended to studies of electronic excitations in semiconductor nanocrystals [33].…”
Section: Methodsmentioning
confidence: 99%
“…VUV excitation luminescence spectroscopy is especially a powerful tool for investigating wide band gap materials such as fluorides [27], iodides [28] and oxides [29][30][31][32]. The method was extended to studies of electronic excitations in semiconductor nanocrystals [33].…”
Section: Methodsmentioning
confidence: 99%
“…Detailed analysis of the emission spectra was done in Ref. 54, taking into account fine structures of both Ce 3þ and Tb 3þ emission bands. It was suggested there that a strong perturbation of the crystal field of rare-earth ions due to a small nanoparticle size leads to the changes in the emission spectra.…”
Section: A Lapo 4 :Cetbmentioning
confidence: 99%
“…[44][45][46] Most of the studies reported in the literature were performed using laser or ultraviolet lamps as an excitation sources, while, for instance, LaPO 4 belongs to the class of wideband-gap materials, and its experimental bandgap was reported to be around 8.0 eV. 47,48 To extend the excitation energy range, in this paper, we use the pulsed synchrotron radiation, which, due to its broad and continuous spectrum, is a very useful tool for the investigation of optical and luminescence properties of wideband-gap materials, [49][50][51][52][53][54] where UV and VUV excitations are dominant.…”
Section: Introductionmentioning
confidence: 99%
“…were frequently reported in the literature, (3)(4)(5) wherein the Tb 3+ and Ce 3+ ions are two important RE ions used to generate green and blue emissions under UV excitation. Green-emitting phosphors such as LaPO 4 (5) were obtained by utilizing a predominant 5 phosphors have been reported and prepared, such as NaBaPO 4 :Ce/Tb, (7,9) NaCaPO 4 Ce/Tb, (8) and LiZnPO 4 :Tb/Ce, (6) which encouraged us to think about the probability of the energy transfer between Ce 3+ and Tb 3+ in the NaSrPO 4 host. The phosphors required a long sintering time to synthesize using the solid-state reaction by conventional sintering.…”
Section: Introductionmentioning
confidence: 99%